St Stephans church viewed from Stock am Eisen, Vienna - Henshall, Josiah (engraver):::Creator::::::::::::; Batty, Robert, 1789-1848 (artist):::Contributor:::::::::::: (London; United Kingdom; Rodwell & Martin ; printed by McQueen & Co.)
View of St. Stephan's church from Stock am Eisen, Vienna